KONSEP GOOD CORPORATE GOVERNANCE DALAM PERSPEKTIF SYARIAH UNTUK MENGATASI PERMASALAHAN PENERAPAN CORPORATE GOVERNANCE PERBANKAN DI INDONESIA - Irham Lutfiansyah; Nadira Paramita; Ummi Itiah Nasution; Juliana Nasution MEI (Universitas 45 Surabaya, 2023)
GCG (Good Corporate Governance) is the most well-known principle in the world to maintain the integrity of the world's organizations. Almost all international location swithin all countries adhere for the basis to build responsibility and openness. Regrettably, in the application, GCG lacks explanation of stakeholder values. That study aims to reconstruct GCG (OECD version) and seek an extra agreeable idea of Sharia Concept. Surely this will provide a solution to the problem it self. After analyzing the value and character of SET, webuild a modern GCG positioned on Islamic concept. These concept ​​are; one; deeper sympathetic of the stakeholder steam, second; principles regarding the rights of stakeholders; third; equality regarding the behavior of stakeholders; fourth; openness principle; last; about corporate accountability. Weak GCG practices in Indonesia are caused by the low level of protection for investors, the class of lawmaintanance, the class of transparency and the ineffective audit committee of public companies. This condition strongly encourages the need for effective and efficient global corporate governance. Islamic Corporate Governance The Islamic perspective lies under the Islamic Corporate Theory which has greater concern for wider stakeholder swhich include God, humans and nature. Differences in goals between conventional Corporate Governance and Sharia GCG which tend to adopt Sharia Enterprise Theory (SET). SET equates material and spiritual values. This shows that GCG Syariah is not only toachieve material benefits, but also spiritual values. SET also equates egoistic values ​​with altruistic values, which in Islamic law are manifested in the form of worship.